Effect of genotypes and nitrogen on grain quality of sorghum - Diallo, Sory (Kansas State University, 2012)
Sorghum (Sorghum bicolor L. Moench) is cultivated as an important food grain in the semi-arid regions of Africa. Processed grain sorghum is traditionally consumed as porridge, couscous, traditional tô or beer. The quality of such foods is highly dependent upon grain characteristics. Sorghum grain quality traits mainly include kernel hardness, kernel weight, kernel size, protein content and kernel color. Grain quality traits are often influenced by environment, genotypes, fertilizer management and their interaction. The objective of this study was to determine the impact of different levels of nitrogen application (0, 45, and 90 kg ha[superscript]-1) on grain quality of selected sorghum genotypes. The field experiment was conducted at three locations in 2010 (Manhattan, Ottawa, and Hays) and at two locations in 2011 (Manhattan and Ottawa). The experiment was laid in split plot randomized complete bloc design and replicated four times. The main plots were assigned to three N regimes: control (0 kg N ha[superscript]-1), half recommended rate (45 kg N ha[superscript]-1) and recommended rate (90 kg N ha[superscript]-1). The subplots were assigned to twelve genotypes (six hybrids and six inbred lines). Plot size was 6.1 m x 3.0 m with a row spacing of 0.75 m. After harvest, grain quality traits (hardness, weight, diameter and protein content) were evaluated using standard procedures and the data subjected to statistical design using SAS. There were significant effects of genotype for most grain quality traits across both locations in Manhattan. Inbred lines SC35 and SC599 had maximum hardness at all locations while hybrid 95207, had the lowest hardness for all locations. Also, Inbred lines SC35 and Tx340 had maximum protein content at all the locations. While hybrids 95207, 26056, 23012 had the lowest protein content. Genotypes Tx430, SC35, had higher hardness and with higher protein content were classified as high quality. We conclude that application of N (45 or 90 kg ha[superscript]-1) significantly improved grain protein, but not other quality traits. There are opportunities to improve grain protein through fertilizer management and plant breeding.
Keywords: Grain quality; Agronomy (0285)